Plug-in-Gait calculation of the knee adduction moment in people with knee osteoarthritis during shod walking: comparison of two different foot marker models. Issue 1 (December 2017) - Paterson, Kade; Hinman, Rana; Metcalf, Ben; Bennell, Kim; Wrigley, Tim
Abstract Background Understanding how kinematic multi-segment foot modelling influences the utility of Plug-in-Gait calculations of the knee adduction moment (KAM) during shod walking is relevant to knee osteoarthritis (OA). Multi-segment foot markers placed on the skin through windows cut in to the shoe provide a more accurate representation of foot mechanics than the traditional marker set used by Plug-in-Gait, which uses fewer markers, placed on the shoe itself. We aimed to investigate whether Plug-in-Gait calculation of the KAM differed when using a kinematic multi-segment foot model compared to the traditional Plug-in-Gait marker set. Methods Twenty people with medial knee OA underwent gait analysis in two test conditions: i) Plug-in-Gait model with its two standard foot markers placed on the shoes and; ii) Plug-in-Gait with the heel marker virtualised from a modified-Oxford Foot Model where 8 ft markers were placed on the skin through windows cut in shoe uppers. Outcomes were the peak KAM, KAM impulse and other knee kinetic and kinematic variables. Results There were no differences (P  > 0.05) in any gait variables between conditions. Excellent agreement was found for all outcome variables, with high correlations (r  > 0.88-0.99, P  < 0.001), narrow limits of agreement and no proportional bias (R 2  = 0.03–0.14, P  > 0.05). The mean difference and 95% confidence intervals for peak KAM were also within the minimal detectable change range demonstrating equivalence. Conclusions Plug-in-Gait calculations of the KAM are not altered when using a kinematic multi-segment foot marker model with skin markers placed through windows cut in to the shoe, instead of the traditional marker set placed on top of shoes. Researchers may be confident that applying either foot model does not change the calculation of the KAM using Plug-in-Gait.